PENGARUH PEMBELAJARAN INKUIRI TERBIMBING BERBASIS LINGKUNGAN TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA MATERI PERTUMBUHAN KELAS V - Elma Wahidatun Nur Rohmah; Rosmiati; Triman Juniarso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the low student learning outcomes on growth material and the level of student understanding is still not at the level of reflective thinking. This study aims to explore the effect of Environment-Based Guided Inquiry learning on students' reflective thinking skills on grade V growth material and describe students' reflective thinking responses after the application of the learning model. This research uses descriptive quantitative research methods. The research was conducted at SDN Kepuh Kiriman 1 Waru Sidoarjo with the subject of VA class 27 students and VB class 29 students. Data collection was done through observation, tests, questionnaires, and documentation. The results showed that the application of the environment-based guided inquiry learning model significantly improved students' reflective thinking skills based on 4 categories of reflective thinking scales, namely Habitual Action, Understanding, Reflection, and Critical Reflection. In experimental class 1, the majority of students' reflective thinking is at the Habitual Action level, where students are already at the level of understanding the material. In experimental class 2, the increase in reflective thinking was in the Habitual Action to Critical Reflection category, and the majority was at the Critical Reflection level where students were able to dig deeper information about the material studied and draw conclusions. The average posttest score of experimental class 1 (VA) was higher than experimental class 2 (VB), with N-Gain showing a high category in both classes. Students' response to this learning model was very positive.